Effect of Freezing Regimens on Protein Aggregation of Human Cord Blood Serum - Nardid, E. O.; Naumenko, E. I.; Rozanova, S. L.; Nardid, O. A. (Problems of Cryobiology and Cryomedicine, 2006)
The effect of different freezing regimens on protein spectrum of cord blood serum has been studied. It has been established that the most favourable conditions are freezing of cord blood serum with the rate not less than 100ºC/min and storage temperature of –80ºC and lower. Cooling rates and storage temperature realized when placing the samples into cooling chambers do not enable the prevention of low temperature aggregation of proteins.